2013
DOI: 10.1097/gox.0b013e3182936cd0
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous PCO2 Measurement at Low Temperature for Reliable and Continuous Free Flap Monitoring

Abstract: Background:Measurement of transcutaneous oxygen pressure (TcPO2) and transcutaneous carbon dioxide pressure (TcPCO2) has been used for free flap monitoring. Because these values are obtained with sensor probes heated to 44°C, there is potential for low-temperature burns on skin flaps. We measured TcPO2 and TcPCO2 at 37°C in both animals and humans to determine the feasibility and safety of the procedure as a postoperative flap monitoring method.Methods:Twelve epigastric island flaps were elevated in rabbits, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 27 publications
0
18
0
Order By: Relevance
“…54,55 Typically when the flap reestablishes the flow after microsurgery, the free flap transcutaneous partial pressure of oxygen level can be as low 10 mmHg in the first few days, whereas the surrounding normal tissue is around 50 mmHg, creating an oxygen gradient that allows inosculation and angiogenesis to occur into the flap, which ultimately allows the flap to survive regardless of the pedicle. 56 Although the initial process may be the same for the free flap used on the ischemic diabetic foot as the transcutaneous partial pressure of oxygen level reaches over 40 mmHg after percutaneous transluminal angioplasty, the ultimate process may differ because the oxygen content of the surrounding tissue usually starts to decline after 3 to 4 weeks, despite the angioplasty. 57 Thus, few studies have reported the idea of the nutrient flap, in which the transferred free flap ultimately serves as the source of the nutrient and capillary network, and only as case reports.…”
Section: Discussionmentioning
confidence: 99%
“…54,55 Typically when the flap reestablishes the flow after microsurgery, the free flap transcutaneous partial pressure of oxygen level can be as low 10 mmHg in the first few days, whereas the surrounding normal tissue is around 50 mmHg, creating an oxygen gradient that allows inosculation and angiogenesis to occur into the flap, which ultimately allows the flap to survive regardless of the pedicle. 56 Although the initial process may be the same for the free flap used on the ischemic diabetic foot as the transcutaneous partial pressure of oxygen level reaches over 40 mmHg after percutaneous transluminal angioplasty, the ultimate process may differ because the oxygen content of the surrounding tissue usually starts to decline after 3 to 4 weeks, despite the angioplasty. 57 Thus, few studies have reported the idea of the nutrient flap, in which the transferred free flap ultimately serves as the source of the nutrient and capillary network, and only as case reports.…”
Section: Discussionmentioning
confidence: 99%
“…25 NIRS can monitor deeper depths, possibly even buried flaps, and is immutable to seroma or hematoma formation. 6,26,27 Although measurement accuracy can be affected by probe movement, the movement must be dramatic. However, NIRS technology cannot provide absolute values and numerous other investigators have found relative trend or index values were better predictors of vascular compromise.…”
Section: Transcutaneous Oxygen Monitoringmentioning
confidence: 99%
“…Currently, the most reliable method is the use of internal Doppler probes, which are placed beside the anastomosis and continuously measure the flow. [2][3][4][5][6][7][8][9][10][11][12][13]19 However, this method is not very popular in some countries such as Mexico because the cost of the device is unaffordable by most health institutions or by the patient. Direct thermography has been well established as a reliable monitoring method and is used in many hospitals worldwide due to its low cost and easy interpretation.…”
Section: Discussionmentioning
confidence: 99%